Reinforcement of polysiloxane/silica elastomer composite by introduction of sacrificial bonds. Issue 15 (27th December 2017) - Zhao, Dannan; Chen, Guowen; Yao, Huiling; Song, Yuanchao
ABSTRACT: It is a challenge to improve tear strength of silicone rubber, especially at high filler loading circumstances. A method is offered here to introduce sacrificial bonds into the system. In particular, amide group was introduced onto the phenyl group of monomer methyl phenyl cyclosiloxane ( D n Ph ) first, and this functionalized monomer ( D n Ph − amide ) was further used for copolymerization with octamethylcyclotetrasiloxane (D4 ) and 2, 4, 6, 8‐tetravinyl‐2, 4, 6, 8‐tetramethyl‐cyclotetrasiloxane ( D 4 Vi ). Vulcanizates composed by this new copolymer (1A‐50) which amide group‐containing is 1 wt % and with 50 phr TS‐530 exhibit high tear strength of about 54 N mm −1, which is three times higher than that composed by polydimethylsiloxane (PDMS)/TS‐530 (50 phr). The mechanical test indicates this new copolymer a promising candidate for the construction of high tear resistant silicone rubber, especially at high filler loading circumstances. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46129. Abstract :